Sharia Investment Literation by Sharia Insurance Agents on Unit-Linked Products - Syarifudin, Syarifudin; Sidarta, Alphasyah Lazuardy; Firdiansyah, Fitra Azkiya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
The growth of the Islamic insurance industry in this country can be seen from the increase in existing assets and players. However, the low level of literacy related to sharia insurance as well as how to invest in unit-linked sharia insurance products makes some people hesitant about sharia insurance. Certified sharia insurance agents are at the forefront of providing investment literacy in sharia insurance products to customers since they have been given full trust to manage their assets so that customers get protection and benefits. How the sharia insurance agent at PT. Asuransi Jiwa Generali Indonesia understands Islamic investment will be discussed in depth using a descriptive qualitative method and triangulation techniques in managing the interview results. This study reveals that certain agents also lack product awareness and investment literacy. So that it can be a reference for insurance agent trainers in optimizing training for agents, both directly and through applications, to provide more understanding and make it easier for Generali insurance agents to provide information on unit-linked products to their customers, especially in terms of sharia investment.